PENGARUH KENAIKAN HARGA BAHAN BAKAR MINYAK (BBM)TERHADAP SEMBILAN BAHAN POKOK (SEMBAKO) - KIRANA, RARA PUSPA; Hidayat, Rusdi; Samsudin, Acep; Sitompul, Stephanie Zefanya; Pradanti, Alsya Puteri; Anugerah, Sven Inggil (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2023)
A commodity that plays an important role in all economic activities is fuel oil (BBM). The direct impact of this change in oil prices is a change in operational costs which results in a corrected level of profit for direct investment activities. In simple terms, the aim of investment is to maximize prosperity through profit, and investors always try to invest in efficient and safe investments. The increase in fuel prices in Indonesia is not only due to the sharp growth of the world oil market, but also because domestic supply is insufficient compared to demand. Of course, the increase in fuel prices has also had an exponential effect on Indonesia's key macroeconomic indicators.